Characterizing runs of homozygosity and their impact on risk for psychosis in a population isolate. Issue 6 (1st July 2014) - Melhem, Nadine M.; Lu, Cong; Dresbold, Cara; Middleton, Frank A.; Klei, Lambertus; Wood, Shawn; Faraone, Stephen V.; Vinogradov, Sophia; Tiobech, Josepha; Yano, Victor; Roeder, Kathryn; Byerley, William; et al.
Abstract An increased abundance of runs of homozygosity (ROH) has been associated with risk for various diseases, including schizophrenia. Here we investigate the characteristics of ROH in Palau, an Oceanic population, evaluating whether these characteristics are related to risk for psychotic disorders and the nature of this association. To accomplish these aims we evaluate a sample of 203 cases with schizophrenia and related psychotic disorders—representing almost complete ascertainment of affected individuals in the population—and contrast their ROH to that of 125 subjects chosen to function as controls. While Palauan diagnosed with psychotic disorders tend to have slightly more ROH regions than controls, the distinguishing features are that they have longer ROH regions, greater total length of ROH, and their ROH tends to co‐occur more often at the same locus. The nature of the sample allows us to investigate whether rare, highly penetrant recessive variants generate such case–control differences in ROH. Neither rare, highly penetrant recessive variants nor individual common variants of large effect account for a substantial proportion of risk for psychosis in Palau. These results suggest a more nuanced model for risk is required to explain patterns of ROH for this population. © 2014 Wiley Periodicals, Inc.